2011
DOI: 10.1089/hum.2010.097
|View full text |Cite
|
Sign up to set email alerts
|

Human Parathyroid Hormone Is Secreted Primarily into the Bloodstream After Rat Parotid Gland Gene Transfer

Abstract: Hypoparathyroidism is a hormone deficiency syndrome that leads to low blood calcium levels and for which current replacement therapy is inadequate. Gene transfer to salivary glands leads to safe and abundant secretion of therapeutic protein into either saliva or the bloodstream. We previously reported the successful transduction of rat submandibular glands with an adenoviral vector encoding human parathyroid hormone (Ad.hPTH), but unfortunately most of the hPTH was secreted into saliva. Because submandibular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Over the last ~15 years we have studied the concept of employing salivary glands as a surrogate endocrine organ using several model human proteins, including α-1-antitrypsin (α1AT), erythropoietin (Epo), growth hormone (GH) and parathyroid hormone (PTH) [4,7,12, 23,24]. While results with α1AT and GH have been relatively straightforward, studies with Epo and PTH were not predictable, with differences in their secretory behavior occurring between certain species and gland types [e.g., 12,2327].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last ~15 years we have studied the concept of employing salivary glands as a surrogate endocrine organ using several model human proteins, including α-1-antitrypsin (α1AT), erythropoietin (Epo), growth hormone (GH) and parathyroid hormone (PTH) [4,7,12, 23,24]. While results with α1AT and GH have been relatively straightforward, studies with Epo and PTH were not predictable, with differences in their secretory behavior occurring between certain species and gland types [e.g., 12,2327].…”
Section: Introductionmentioning
confidence: 99%
“…While results with α1AT and GH have been relatively straightforward, studies with Epo and PTH were not predictable, with differences in their secretory behavior occurring between certain species and gland types [e.g., 12,2327]. Unfortunately, little is known about the mechanisms responsible for the sorting of secretory proteins in polarized epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the epithelium of these organs can be easily accessed from the oral cavity in a non-invasive fashion, by introducing fine polyethylene tubing into the major excretory ducts (Wharton’s duct in the submandibular glands and Stensen’s duct in the parotid glands). This route, that has been utilized to selectively deliver various molecules into the ductal system, has been extensively characterized for both viral- and non viral-mediated gene transfer both in animals and in humans (Adriaansen et al, 2008; Adriaansen et al, 2011; Adriaansen et al, 2010; Baccaglini et al, 2001; Baum et al, 2006; Delporte et al, 1997; Gao et al, 2011; Goldfine et al, 1997; Honigman et al, 2001; Niedzinski et al, 2003a; Niedzinski et al, 2003b; Perez et al, 2011; Samuni et al, 2008; Xu et al, 2010; Zheng and Baum, 2011; Zheng and Baum, 2005; Zheng et al, 2011a; Zheng et al, 2006; Zheng et al, 2011b; Zheng et al, 2011c). Second, we have shown that salivary glands are ideal organs to perform intravital microscopy, which enables imaging various biological processes in live animals (Masedunskas et al, 2012; Masedunskas et al, 2011; Masedunskas and Weigert, 2008; Sramkova et al, 2009; Weigert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that SGs are able to produce pharmacological levels of growth hormone and parathyroid hormone following transduction with recombinant viral vectors [30], [31]. A phase I clinical trial targeting gene transfer to the salivary glands for treating radiation induced xerostomia was initiated and a total of 11 patients have been treated with all reporting tolerance of the vector and procedure [32].…”
Section: Introductionmentioning
confidence: 99%